A recategorização como processo de construção de objetos de discursos: quando grafitar é transformar a realidade - Oliveira, Francisca Poliane Lima de (2018)
Through the reports we have on writing, throughout history, graffiti has been living with us for a long time. Today, these brands “express with traces, letters and drawings, the contradictions implied in the contemporary urban experience”. From this premise we are dedicated to analyzing a work that has caught our attention because of its peculiarity in terms of production. In order to do so, we adopt a dynamic conception of text - in which it is seen as a communicative event (BEAUGRANDE, 1997) - and also of a notion of recategorization that points beyond textual materiality (COSTA, 2007; JAGUARIBBE, 2007). In addition to the observations about doing in this specific work, we also seek to show the power of social transformation, cognitive and aesthetic that graffiti can operate in reality. To study more closely a situation of textual production like the one we brought here, made us see how the discretization of the world in the speeches takes place and how the union of life with art takes place. Taking the example of this analysis as we have done here has helped us to think carefully about this characteristic of dynamism of the language productions about which we have been speaking and still to show that recategorization is a process that also occurs at an extratextual level, about reality.